Production and properties of spray dried Clinacanthus nutans using modified corn starch as drying agent - Mohamad Azman, Ezzat; K., Abetra; Mohd Adzahan, Noranizan; Yusof, Noor Liyana (Rynnye Lyan Resources, 2020)
Clinacanthus nutans leaves is a medicinal plant with promising therapeutic effect. The objective of this study was to produce C. nutans powder using a spray dryer and to evaluate its physicochemical properties, followed by physical observation after 3 months of storage at room temperature (21±1°C). C. nutans juice with and without the addition of 5% (w/v) of modified corn starch (MCS) was spray dried at a feed flow rate of 23 rpm, inlet air temperature of 160°C and outlet air temperature of 100°C. Results showed that significantly lower (p <0.05) values of water activity, moisture content, flowability, particle size, solubility, wettability and dispersibility times, while significantly higher (p<0.05) values of hygroscopicity, bulk and tapped densities were recorded as compared to the spray dried powder without the addition of MCS. These indicated that MCS as drying agent has significantly improved the powder properties and the physical appearance during storage. Furthermore, produced C. nutans powder had a significantly higher (p<0.05) IC50 values, percentage of inhibition and total phenolics content. Also, a strong correlation was observed between total phenolic and antioxidant activity, indicated that encapsulation using MCS successfully protected the thermally sensitive compounds which contributed to high antioxidant activity.